A Study of Problems Faced by Farmers in Raigad District of Maharashtra - Dr. Trupti Sandeep Thorat (International Journal of New Media Studies: International Peer Reviewed Scholarly Indexed Journal, 2023)
The primary goal of this study is to understand the issues facing farmers in the agriculture industry. The main good for ensuring life quality is food products and wellness. Farmers are the foundation of the global economy because so many nations rely on the agricultural sector.